Intelligence quotient improves after antiepileptic drug withdrawal following pediatric epilepsy surgery. Issue 1 (July 2015) - Boshuisen, Kim; van Schooneveld, Monique M. J.; Uiterwaal, Cuno S. P. M.; Cross, J. Helen; Harrison, Sue; Polster, Tilman; Daehn, Marion; Djimjadi, Sarina; Yalnizoglu, Dilek; Turanli, Guzide; Sassen, Robert; Hoppe, Christian; et al.
<x xml:space="preserve">Abstract</x> Objective Antiepileptic drugs (AEDs) have cognitive side effects that, particularly in children, may affect intellectual functioning. With the TimeToStop (TTS) study, we showed that timing of AED withdrawal does not majorly influence long‐term seizure outcomes. We now aimed to evaluate the effect of AED withdrawal on postoperative intelligence quotient (IQ), and change in IQ (delta IQ) following pediatric epilepsy surgery. Methods We collected IQ scores of children from the TTS cohort with both pre‐ and postoperative neuropsychological assessments (NPAs; n = 301) and analyzed whether reduction of AEDs prior to the latest NPA was related to postoperative IQ and delta IQ, using linear regression analyses. Factors previously identified as independently relating to (delta) IQ, and currently identified predictors of (delta) IQ, were considered possible confounders and used for adjustment. Additionally, we adjusted for a compound propensity score that contained previously identified determinants of timing of AED withdrawal. Results Mean interval to the latest NPA was 19.8 ± 18.9 months. Reduction of AEDs at the latest NPA significantly improved postoperative IQ and delta IQ (adjusted regression coefficient [RC] = 3.4, 95% confidence interval [CI] = 0.6–6.2, p = 0.018 and RC = 4.5, 95% CI = 1.7–7.4, p = 0.002), as did complete withdrawal (RC = 4.8, 95% CI = 1.4–8.3, p = 0.006 and RC = 5.1, 95% CI = 1.5–8.7, p = 0.006). AED reduction also predicted ≥10‐point IQ increase (p = 0.019). The higher the number of AEDs reduced, the higher was the IQ (gain) after surgery (RC = 2.2, 95% CI = 0.6–3.7, p = 0.007 and RC = 2.6, 95% CI = 1.0–4.2, p = 0.001, IQ points per AED reduced). Interpretation Start of AED withdrawal, number of AEDs reduced, and complete AED withdrawal were associated with improved postoperative IQ scores and gain in IQ, independent of other determinants of cognitive outcome. Ann Neurol 2015;78:104–114